Supercritical carbon dioxide extraction as an alternative method to extract natural bioactive compounds - Ananda Regita Olivira; Hadi Munarko; Jariyah Jariyah; Liza Md Salleh (AGROINTEK, 2025)
The study regarding the extraction of bioactive compounds from natural sources such as phenolics, flavonoids, and carotenoids has received significant attention, because these bioactive compounds known to have numerous benefits for human health. Various extraction methods have been used to obtain bioactive compounds. However, the conventional extraction method that is often used has several drawbacks including the use of large amounts of solvent and longer extraction time. Therefore, an alternative extraction method is needed to overcome the limitations of conventional methods. Extraction using supercritical carbon dioxide is an alternative extraction method that is more efficient with a shorter extraction time. This article aims to provide a comprehensive review regarding the extraction of bioactive compounds using supercritical carbon dioxide (SC-CO2). The use of low critical temperature and pressure during SC-CO2 extraction prevents the degradation of the bioactive components. In addition, because of its high selectivity, SC-CO2 extraction can produce a maximum yield with high purity of bioactive components. Therefore, extraction using supercritical carbon dioxide has the opportunity to be used as an alternative method to maximize the extraction process of bioactive compounds.